ANALISIS KOMPARATIF KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS PADA PT EAGLE HIGH PLANTATIONS TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Irdian, Irdian; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study amis to analyze and compare financial performance based on liquidity, solvency and profitability ratios at PT Egle High Plantations Tbk listed on the Indonesia Stock Exchange for the period 2019-2023. The data used in this study are secondary data in the form of annual financial statements. The research method used is a comparative method with a quantitative approach. Data analysis techniques use financial ratios including Current ratio to measure liquidity, Debt to Equity Ratio to measure solvency, and Return on Assets to measure profitability. The result show that the company’s financial performance fluctuated during the study period. Liquidity ratios indIcate an unstable ability to meet short-term obligations. Solvency ratios show a relatively high dependence on debt . Meanwhile, profitability ratios indIcate that the company’s ability to generate profits is still not optimal. This research is expected to provide consideration for management and investors in decision-making.